Delays in stabilization or in reforms? The debt crisis - Cinquetti, Carlos Alberto [UNESP]; Silva, Ricardo Goncalves (Blackwell Publishing, 2008)
Empirical analyses attributing the 1980s' debt crisis to inconsistent stabilization policies rest on an inappropriate long-run approach. Revising this long-run approach yields opposite results: terms of trade shocks and foreign indebtedness explain this crisis, regardless of domestic stabilization policies. This prompts us to consider a new hypothesis, of delays in trade-policy reforms, with a model in which terms-of-trade variation (under shocks) is endogenous to export structure and efficiency of resource allocation. Evidence from the structural equations model shows that allocation distortions negatively affect changes in terms of trade, which then explain this crisis. A political economy extension demonstrates that income inequality and regional trade policy determine the distortions, which in turn leads to this crisis.
Keywords: debt crisis; shocks; stabilization policies; trade policies; inequality; structural equations